2012
DOI: 10.1186/1471-2369-13-152
|View full text |Cite
|
Sign up to set email alerts
|

Who should be prioritized for renal transplantation?: Analysis of key stakeholder preferences using discrete choice experiments

Abstract: BackgroundPolicies for allocating deceased donor kidneys have recently shifted from allocation based on Human Leucocyte Antigen (HLA) tissue matching in the UK and USA. Newer allocation algorithms incorporate waiting time as a primary factor, and in the UK, young adults are also favoured. However, there is little contemporary UK research on the views of stakeholders in the transplant process to inform future allocation policy. This research project aimed to address this issue.MethodsDiscrete Choice Experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
(46 reference statements)
0
19
1
Order By: Relevance
“…The composition of the studies was heterogeneous; although just over half of the studies (n=20) compared one group of healthcare providers with either patients (or in the case of screening, those who had experienced the test) 9 32 34 36 38 40–45 47 54 55 58 60 61 64 65 or the general population, 31 12 studies compared the preferences of patients 33 35 37 46 48 49 51 52 56 57 67 or parents of patients 39 with multiple healthcare providers, and the remainder varied in either their non-healthcare provider 53 59 63 or both non-healthcare provider and healthcare provider groups. 50 62 66 …”
Section: Resultsmentioning
confidence: 99%
“…The composition of the studies was heterogeneous; although just over half of the studies (n=20) compared one group of healthcare providers with either patients (or in the case of screening, those who had experienced the test) 9 32 34 36 38 40–45 47 54 55 58 60 61 64 65 or the general population, 31 12 studies compared the preferences of patients 33 35 37 46 48 49 51 52 56 57 67 or parents of patients 39 with multiple healthcare providers, and the remainder varied in either their non-healthcare provider 53 59 63 or both non-healthcare provider and healthcare provider groups. 50 62 66 …”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] For example, in a discrete choice experiment about renal transplantation, respondents preferred policies that recognized the importance of recipient age, societal responsibilities, time on the waitlist, life expectancy, and posttransplant quality of life. 9,10 Another study of priorities for patients with renal failure in receiving kidneys identified preferences for "enhancing life, medical priority, recipient valuation, and deservingness." 11 In some cases, public opinion conflicts with generally accepted medical ethics, for example, when a surveyed population felt that allocation should depend on whether patients caused their own disease.…”
Section: Introductionmentioning
confidence: 99%
“…Thus evaluation of cost‐effectiveness is a key factor for new healthcare technologies. Professor Ala Szczepura has published widely on health economics, including a recent study looking at allocation of deceased donor kidneys for transplantation (Clark et al ., ).…”
Section: Transplant Infectious Disease Workhop 24th November 2012mentioning
confidence: 97%